The influence of test preparation programs on IELTS test performance among Bangladeshi students' studying in Malaysia - Aktar, Ayesha; Noordin, Nooreen; Ismail, Lilliati (Universiti Putra Malaysia, Universiti Pertanian Malaysia Press, 2021)
Test preparation programs namely coaching, mock tests, and repetitive test-taking aid students in achieving language skills and comprehending the International English Language Testing System (IELTS) test procedure. This paper attempted to find out the influence of test preparation programs on candidates’ IELTS test performance. A quantitative method was used, and an online questionnaire survey was conducted to obtain the data. The population of the study was the Bangladeshi students at Universiti Putra Malaysia. Probability sampling, specifically simple random sampling techniques were used to draw the sample. Data were collected from a total of 100 students, and SPSS was employed to analyze the data. The finding showed that mock test (r = 0.450), coaching (r = 0.496), and repetitive test-taking (r = 0.369) have a positive and moderate correlation with IELTS test performance. In contrast, the mock test, coaching, and repetitive test-taking have 23.4%, 35.3%, and 21.3% influence on IELTS test performance, respectively. This study has implications for candidates’ teaching and learning opportunities for competitive English language test programs. Furthermore, it will deliver a diverse viewpoint on the preparation programs and show their effectiveness for future reference. This study can be used as a guideline for future research to improve test preparation programs for better test performance.